The Use of Angklung as a Medium for Preserving Traditional Musical Instruments in Early Childhood (Ages 5-6) - Lailatuz Hasanah; Sarah Emmanuel H; Henni Anggraini (CV. Creative Tugu Pena, 2024)
Indonesia is known as a country rich in culture, including traditional music, which serves as a national identity and asset. However, the current of globalization has brought significant challenges to the preservation of local culture, especially among the younger generation. This study aims to describe the use of angklung as a medium for preserving traditional musical instruments among early childhood students at Mambaul Ulum Gondanglegi Kindergarten. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The results showed that regular angklung playing activities can increase children's interest in local culture and support their cognitive, motor, socio-emotional, and character development. Children aged 5–6 years showed high enthusiasm in participating in angklung activities, which were packaged in a fun and contextual manner appropriate to their developmental stage. In addition to being a musical instrument, angklung has proven effective as a means of character education and a medium for cultural preservation integrated into early childhood learning activities. These findings underscore the importance of integrating traditional arts into the educational curriculum as a strategy to foster children's love of national culture from an early age.